BIOSTIMULYATORLARNING HAYVONLAR IMMUN TIZIMIGA TA’SIRI - Jumaqulova, Guzal; Rasulova, S.L.; Shavkatova, X.R (MODERN PROBLEMS AND PROSPECTS FOR ORGANIZING A HEALTHY LIFESTYLE AND PROPER NUTRITION, 2024)
BIOSTIMULYATORLARNING HAYVONLAR IMMUN TIZIMIGA TA’SIRI